2014
DOI: 10.1186/s12917-014-0252-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of preoperative tramadol and pethidine on postoperative pain in cats undergoing ovariohysterectomy

Abstract: BackgroundA variety of analgesic agents are available, and which one can be used in dogs and cats is a highly controversial issue, existing however a fear in the use of opiates due to possible adverse effects that these drugs can cause. The aim of this study was to compare the analgesic effect provided by the administration of tramadol or pethidine on early postoperative pain of cats undergoing ovariohysterectomy in a double-blind prospective study. Fourty-two animals were randomly assigned into three groups. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 37 publications
1
38
0
2
Order By: Relevance
“…When considering postoperative analgesic supplementation, few cats (6 out of 45 cats) required rescue analgesia. In the S group, rescue analgesia was given in 4 cats (27%), which is in agreement with previous studies that reported a prevalence of rescue analgesia between 13 and 50% after ovariohysterectomy in cats treated preoperatively with an opioid alone or combined with meloxicam [4,24]. Although the frequency of recue analgesia did not differ among treatments, only one cat in each R and RM groups required supplemental analgesics, indicating that both protocols of local analgesia provided was some analgesic benefit when compared to saline controls.…”
Section: Discussionsupporting
confidence: 90%
“…When considering postoperative analgesic supplementation, few cats (6 out of 45 cats) required rescue analgesia. In the S group, rescue analgesia was given in 4 cats (27%), which is in agreement with previous studies that reported a prevalence of rescue analgesia between 13 and 50% after ovariohysterectomy in cats treated preoperatively with an opioid alone or combined with meloxicam [4,24]. Although the frequency of recue analgesia did not differ among treatments, only one cat in each R and RM groups required supplemental analgesics, indicating that both protocols of local analgesia provided was some analgesic benefit when compared to saline controls.…”
Section: Discussionsupporting
confidence: 90%
“…Tramadol is also commonly used to treat pain in cats. In contrast with dogs, studies in cats (although fewer) have consistently demonstrated efficacy (Pypendop et al, 2009;Evangelista et al, 2014), which may be a consequence of the relatively high circulating M1 concentrations reported in cats after tramadol administration (Pypendop et al, 2009;Cagnardi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported an increase in cortisol levels compared to baseline preoperative values (MÖLLENHOFF et al, 2005) and in cats with higher pain scores and requiring rescue analgesia (EVANGELISTA et al, 2014). However, in another study differences in physiological parameters including cortisol and β-endorphins were not observed between cats that had undergone surgery and control cats (that had not) (CAMBRIDGE et al, 2000).…”
Section: Pain Recognitionmentioning
confidence: 65%